Alternative and off-label use of Titanium Elastic Nail® in acute adult humeral diaphyseal and subcapital fractures - C.E.M. Pothmann (Elsevier, 2021)
Traumatic adult humeral diaphyseal fractures can be difficult to deal with in geriatric patients. Three examples are summarized in using Titanium Elastic Nails® (TEN) in adult patients as an efficient alternative and an off-label strategy in treating diaphyseal as well as subcapital humeral fractures.A 75 years old adult female patient suffering from a motor neuron disease with flail arm syndrome and symmetric limp paraparesis of the arms with missing reflexes of arms and legs. Plain film radiographs demonstrated a multifragmentary fracture of the diaphysis of the right humerus with slight dislocation. After fail of an initial conservative therapy attempt, the fracture was splinted intramedullary with two titanium elastic nails until fracture healing.A 59 years old female patient slipped and fell at ground level on her left side. An oblique diaphyseal humeral fracture was found. Due to an anticoagulation with clopidogrel and a major rotator cuff lesion an immediate operation was performed by minimally invasive intramedullary titanium elastic nailing. Two and a half months after surgery the fracture was fully consolidated, full weight bearing was possible four months after the surgery. The implant removal was performed five and a half months after the initial trauma without postoperative complications with full recovery of the patient and restitutio in integrum.A young female skier fell on the ski field and sustained a subcapital humerus fracture on the left side. As a primary wish of the patient getting the most minimally invasive and scar free operation, an off-label use of Titanium Elastic Nail® (TEN) was chosen and performed.The postoperative stability did allow an adequate early functional training with initially passive and active assistive motion.In conclusion, intramedullary titanium elastic nailing can be a sufficient minimally invasive technique in patients with secondary diagnoses influencing operability, bone structure and fracture healing.